The ichthyofauna of drifting macrophyte mats in the Ivinhema River, upper Paraná River basin, Brazil - Bulla,Cíntia Karen (2011)
We describe the fish assemblages associated with drifting macrophyte mats and consider their possible role as dispersal vectors in the Ivinhema River, a major tributary of the upper Paraná River, Brazil. Fish associated with drifting mats were sampled in the main river channel during January and March 2005, when the wind and/or the increased water level were sufficient to transport macrophyte stands. Fish in the drifting mats were sampled with a floating sieve (4 m long x 2 m wide x 0.6 m high, and 2 mm mesh size). In the laboratory, larvae, juvenile, and adult fish were counted and identified to the lowest possible taxonomic level. In four drifting macrophyte mats we captured 218 individuals belonging to at least 28 species, 17 families, and 6 orders. Aphyocharax dentatus, Serrasalmus spp., and Trachelyopterus galeatus were the most abundant taxa associated with the mats, but species richness ranged from 6 to 24 species per mat. In addition, 85% of the total number of individuals caught was larvae and juveniles. Although preliminary and based on limited samples, this study of drifting macrophyte mats was the first one in the last unregulated stretch of the Paraná River remaining inside Brazilian territory, and alerts us to the potential role of macrophytes mats as dispersers of fish species in the region.